Addressees as protagonists of reading book stories: children and their portrayal – a comparison of an Italian storybook for Italian – language schoolchildren during the Imperial and Royal Habsburg era and a German storybook for German-language schoolchild - Augschöll Blasbichler, Annemarie (Rivista di Storia dell’Educazione, 2018)
Schoolbooks are written for children. The stories and narratives they contain are a self-representation of society and its values and visions. This paper analyzes the texts in two textbooks written for children of a minority language in Trentino and in South Tyrol in the historical context of nationalist settings in the early 20th century. The focus of interest lies in the representation of child protagonists in the stories and narratives.